2001
DOI: 10.1177/106342660100900301
|View full text |Cite
|
Sign up to set email alerts
|

The Distal Impact of Two First-Grade Preventive Interventions on Conduct Problems and Disorder in Early Adolescence

Abstract: In this article, we examine the impact of two universal, first-grade preventive interventions on the prevalence of conduct problems and disorder and mental health service need and use in early adolescence. The classroom-centered (CC) intervention was designed to reduce the risk for later conduct problems and disorder by enhancing teachers' behavior management in first grade, whereas the Family-School Partnership (FSP) intervention targeted improvement in parent-teacher communication and parents' child behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
194
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(211 citation statements)
references
References 35 publications
10
194
0
4
Order By: Relevance
“…The medium size of effect of the reductions in externalizing behavior after 2 years of intervention (d ϭ 0.45) can be regarded as substantial considering that the GBG is a universal preventive intervention. This significant reduction in externalizing behavior adds to previous findings on the effectiveness of the GBG in reducing externalizing behavior (Embry, 2002;Ialongo et al, 2001;Kellam et al, 2008Kellam et al, , 1994Petras et al, 2008;van Lier et al, 2004). We found that reductions in externalizing behavior were specific for boys.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The medium size of effect of the reductions in externalizing behavior after 2 years of intervention (d ϭ 0.45) can be regarded as substantial considering that the GBG is a universal preventive intervention. This significant reduction in externalizing behavior adds to previous findings on the effectiveness of the GBG in reducing externalizing behavior (Embry, 2002;Ialongo et al, 2001;Kellam et al, 2008Kellam et al, , 1994Petras et al, 2008;van Lier et al, 2004). We found that reductions in externalizing behavior were specific for boys.…”
Section: Discussionsupporting
confidence: 77%
“…Because of the active facilitation and rewarding of positive interactions between team members, it is reasonable to assume that these changes in positive peer interactions underlie the effect of the program on externalizing problems. Previous research on the GBG found that the program was indeed effective in reducing externalizing behavior (Ialongo, Poduska, Werthamer, & Kellam, 2001;Kellam et al, 2008;Kellam, Rebok, Ialongo, & Mayer, 1994;Petras et al, 2008;van Lier, Muthén, van der Sar, & Crijnen, 2004). Given these findings, we hypothesize to find reductions in externalizing behavior after 2 years of intervention among GBG children in the present trial, as compared with control-group children.…”
Section: The Present Studymentioning
confidence: 95%
“…(For more information on intervention effects, see [23,24,36,55]). The initial sample of 678 children was representative of students entering first grade in one of nine Baltimore City public schools in the fall of 1993.…”
Section: Samplementioning
confidence: 99%
“…A randomized block design was employed, with schools serving as the clustering factor. Details about the sample design and trial are available elsewhere [5]. In 2004, when most of the cohort was in 11th grade, 73% (n=232) of the original female cohort participated in a 60-90 minute self-administered computer with audio interview: 90% African American, mean age 17.0 years.…”
Section: Samplementioning
confidence: 99%
“…and aggression [5]. A randomized block design was employed, with schools serving as the clustering factor.…”
Section: Samplementioning
confidence: 99%